Polymeric Hydrogel Nanocapsules: A Thermo and pH Dual-responsive Carrier for Sustained Drug Release - Nan, Jingya; Chen, Ying; Li, Rutian; Wang, Jifu; Liu, Meihong; Wang, Chunpeng; Chu, Fuxiang (Nano-Micro Letters, 2014)
Hydrogel capsules show attractive prospects in drug delivery recently because of high drug loading and sustained release behavior. In this study we reported a simple and convenient route to fabricate poly (acrylic acid)-poly (N-isopropylacrylamide) (PAA-PNIPAm) hydrogel capsules by using hydroxypropylcellulose-poly (acrylic acid) (HPC-PAA) complexes as the templates. The capsules showed a high drug loading (∼280% to the weight of capsules) for Doxorubicin hydrochloride. The release of drug from the capsules was responsive to the temperature and pH of the surroundings, showing a low-rate but sustained release behavior favorable for low-toxic and long-term therapy. Together with the convenient preparation, high drug loading, dual responsivity as well as the sustained release feature, it is implied that this polymeric hydrogel capsule might be a promising candidate for new drug carriers.